2021
DOI: 10.1016/j.ymssp.2020.107264
|View full text |Cite
|
Sign up to set email alerts
|

An exact dynamic stiffness method for multibody systems consisting of beams and rigid-bodies

Abstract: An exact dynamic stiffness method is proposed for the free vibration analysis of multi-body systems consisting of flexible beams and rigid bodies. The theory is sufficiently general in that the rigid bodies can be of any shape or size, but importantly, the theory permits connections of the rigid bodies to any number beams at any arbitrary points and oriented at any arbitrary angles. For beam members, a range of theories including the Bernoulli-Euler and Timoshenko theories are applied. The assembly procedure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…in a unique LFT model. The peculiarity of the TITOP theory with respect to similar substructure approaches in literature as [11,12] consists in providing dynamical models directly adapted for robust performance certification and robust control synthesis.…”
Section: Background and Motivationmentioning
confidence: 99%
“…in a unique LFT model. The peculiarity of the TITOP theory with respect to similar substructure approaches in literature as [11,12] consists in providing dynamical models directly adapted for robust performance certification and robust control synthesis.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Specific methods have been developed for systems with certain features. An exact calculation method using dynamic stiffness was used to analyze vibrations of multibody systems with flexible beams connecting rigid bodies [30]. Rigid bodies can have any geometry and can have connections between them by means of elastic beams.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [19] suggested a new method for calculating the stiffness of bolted connectors and analyzed the effects of joint surface stiffness on the overall stiffness. Liu et al [20] developed an exact dynamic stiffness method for multi-body systems composed of beams and rigid bodies.There are two main types of robot stiffness modeling, namely, finite element (FE) [21] and analytical [22] methods. FE methods can describe aspects, such as the structural geometric dimensions, physical material properties, contact conditions, and load distribution, of robots in a comprehensive and detailed manner.…”
Section: Introductionmentioning
confidence: 99%